Probing the Effect of Protein and Inhibitor Conformational Flexibility on the Reaction of Rocelitinib-Like Covalent Inhibitors of Epidermal Growth Factor Receptor. A Quantum Mechanics/Molecular Mechanics Study - Orathai Kaewkham; Duangkamol Gleeson; Poowadon Fukasem; Jirapat Santatiwongchai; Donald J. L. Jones; Robert G. Britton; M. Paul Gleeson (My University, 2025)
Epidermal growth factor receptor (EGFR) is a tyrosine kinase and a validated target for non-small cell lung cancer (NSCLC). Drug discovery efforts on this target initially focused on traditional competitive, reversible ATP-binding site inhibitors; however, irreversible covalent binding EGFR inhibitors have become increasingly more popular. Covalent EGFR inhibitors have been developed using a range of different scaffolds, and unsurprisingly, the incorporation of an electrophilic acrylamide group can result in sizable orientation differences relative to the Cys797 nucleophile and the Asp800 general base. In this work, we report a QM/MM study aiming to better understand the aspects of covalent adduct formation, including the role of protein flexibility on chemical reactivity, the impact of electrophile location within the ATP binding site, and the impact of the acrylamide conformation (s-cis vs s-trans). We focus here on the diaminopyrimidine scaffold, as exemplified by Rocelitinib, where the electrophile is attached to its back pocket binding group. Our goal is to elucidate how electrophilic groups can be incorporated onto different inhibitor scaffolds targeting reactive active site residues. We find that irrespective of the EGFR MD conformation chosen, acrylamide, in both the s-cis or s-trans, can undergo reaction with rate-determining barriers of ∼20 kcal/mol. Interestingly, the nature of the rate-determining step for Rocelitinib-like inhibitors was found to be either direct nucleophilic attack or keto–enol tautomerization, depending on the precise protein and inhibitor conformation.
Keywords: Molecular mechanics; Chronic Lymphocytic Leukemia Research